Exploring Taste: The Influence of Eating Styles on Food Choice Motives - Rahamawati, Lusy; Undarwati, Anna (Universitas Ahmad Dahlan, 2025)
The high prevalence of obesity has made individuals more cautious in choosing food. Many of them are now beginning to consider their physical health, such as maintaining their weight. This study aims to determine the influence of eating patterns on food choice motives. The research method used is quantitative, involving the distribution of questionnaires. The study participants consisted of 206 students in the city of Semarang, and data analysis was conducted using the Multivariate GLM Test. The results of this study indicate that controlled eating patterns influence weight control, external eating patterns influence sensory appeal, but emotional eating patterns don’t influence food choice motives. In conclusion, both eating patterns among students significantly influence food choice motives. Specifically, controlled eating patterns affect weight control, external eating patterns affect sensory appeal, but emotional eating patterns don’t affect both dependent variables (weight control and sensory appeal).